2012
DOI: 10.1103/physreve.85.051703
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced anchoring on a chalcogenide surface

Abstract: We present basic characteristics and a model of photoinduced anchoring of liquid crystals (LCs) on a chalcogenide surface. It was found that characteristics of the alignment strongly depend on the LC material for the same chalcogenide glass. The photoalignment is partially reversible and can be controlled by changing the light polarization direction. We propose a model in which the existence of dichroic units on the chalcogenide surface and competition between two mechanisms of the photoalignment is suggested.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…According to Ref. [15], this time is associated with the time needed for settling equilibrium for the angular distribution of adsorbed LC molecules on the photosensitive surface during the irradiation process.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ref. [15], this time is associated with the time needed for settling equilibrium for the angular distribution of adsorbed LC molecules on the photosensitive surface during the irradiation process.…”
Section: Resultsmentioning
confidence: 99%
“…The easy orientation axis is either parallel or perpendicular to the polarization of the excitation beam [26][27][28]. In both cases, the light-induced easy axis on the chalcogenide surface ⃗ ex is described by the same expression as Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The origin of this easy orientation axis can be either light-induced desorption of LC molecules from the chalcogenide surface [26] and/or light-induced anisotropy in the chalcogenide film [27,28]. The easy orientation axis is either parallel or perpendicular to the polarization of the excitation beam [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently a new class of photoaligning materials based on chalcogenide glasses was introduced [17][18][19][20][21][22][23][24][25]. Kurioz et al observed photoalignment of a nematic LC on a chalcogenide surface upon polarized light irradiation through a layer of LC in the isotropic phase in a cell [17].…”
Section: Introductionmentioning
confidence: 99%